Effectiveness of Tuba Root Extract Dosage (Paraderris elliptica) to Gold Fish Oxygen Consumption Rate (Carassius auratus) on Transportation Closed - Devani, Khairul; Febri, Suri Purnama; Haser, Teuku Fadlon; Aprita, Ika Rezvani; Nazlia, Suraiya; Antoni, Antoni; Fuadi, Afdhal; Azmi, Fauziah (Jurnal Perikanan Terpadu, 2024)
Chef carp (Carassius auratus) is a freshwater ornamental fish that is one of the ornamental fish that is widely cultivated because it has a diverse body shape and has a variety of colors. The problem often faced by carp suppliers in the process of distributing fish with a closed fish transportation system is low survival pass. The use of such anesthesia materials is quite effective in closed transport systems. One of the natural compounds that can be used as an anesthetic agent is rotenon. The roots of tubal plants contain rotenon, a powerful poison for fish and insects. The method used in this study is an experimental method, this study uses Complete Randomized Design (CRD) with 4 treatments and 3 repeats. The dose of tubal root extract used was P1 (control), P2 (0.10 ml / L), P3 (0.15 ml / L), P4 (0.20 ml / L). The density of fish per plastic bag amounts to 10 heads with a transportation time of 9 hours. The parameters observed were length of intoxication time, survival rate, length of time recovered consciously, oxygen consumption rate and water quality. Giving doses of tubal root extract with different doses had a significant effect (P<0.05). The highest survival rate value in P2 treatment with a dose of 0.10 ml and saving the rate of oxygen consumption with the right dose is in P4 with a dose of 0.20 ml / L ranging from 0.039 mg O2 / minute.